Things I overheard while talking to myself [compact disc, unabridged] - Alda, Alan, 1936- (Random House Audio, 2007)
The popular actor looks back to reassess the meaning of his own life and the paths he has taken, from the turbulent 1960s to the tragedy of September 11, and to answer such questions as "What do I value?" and "What, exactly, is the good life?"